AXIOLOGICAL BASES OF PUBLIC SERVICE ANNOUNCEMENTS AS A RESOURCE MANAGEMENT OF SOCIAL DEVELOPMENT - Bulba V.H.; Fedchenko О.V. (Pressing Problems of Public Administration, 2015)
The problems valuable content of public service announcements, the place in theimplementation of the social functions of the state and prospects for use in the management ofsocial development.